The Impact Of Uplift Forces On The Connection Of Steel Cladding For Rural Houses In Malaysia - Akramah, Hamzah Atef (Universiti Sains Malaysia, 2021)
The research of the impact of wind uplift forces and pressures on the steel cladding and the fastener behaviour for the rural houses is the focus of the study. Based on a recent survey done on the damaged roofing system in the rural houses due to heavy windstorm affected many locations in Malaysia, showed that steel roof cladding sheets was the most affected part of the building. The rural areas in Malaysia have a huge number of non-engineered houses where the roof made out from the affordable material especially the steel roof cladding such as trapezoidal and corrugated. The connection between the purlin cladding used a fastener namely a nail or screw. Most of previous studies on this field were focusing on the low rise engineered building, which followed the engineering building codes, while this study only focused on the houses built with no or limited engineering guidance. The research adopted the numerical study method using ANSYS workbench software, via the static structure subsection to simulate the steel roof cladding and the fasteners. The finite element models subjected to several values of uplift forces, which are 5, 6, and 7kN for trapezoidal steel cladding, whereas, due to the curvy shapes of the corrugated steel cladding where the uplift forces were replaced by the uplift pressures which are 3.8, 4.6, and 5.3kPa. The study suggested adding a strip with different widths, 75mm, 100mm and 150mm near the central fastener, where the most critical stress usually occurred and highest deflection recorded. The results show a sufficient improvement regarding the deformation of the steel cladding and the fastener reaction force. The use of additional strip method has reduced the effect of wind uplift forces by 27% - 82% and the pull through capacity increases by 22% - 54% for the fastener. The additional strip presence showed a large impact which will lead to protect the steel roof cladding connection from failure where it is the most critical part of the roofing system.